2016
DOI: 10.4314/ahs.v15i4.15
|View full text |Cite
|
Sign up to set email alerts
|

Low serum 25(OH)D levels are assocıated to hıgher BMI and metabolic syndrome parameters in adult subjects in Turkey

Abstract: Background: The aim of this study was to investigate the association of 25(OH)D levels with biochemical, anthropometric, and metabolic data obtained from normal and obese people. Methods: This study was carried out on 90 individuals between the ages of 18 to 63 that had various body mass indexes. Blood samples and anthropometric measurements were taken. Results: Waist circumferences, fat mass, LDL cholesterol levels, HDL cholesterol levels, 25(OH)D levels, and triglyceride levels were significantly different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 53 publications
(52 reference statements)
1
28
2
Order By: Relevance
“…One study including subjects in Korea also showed a negative relation between 25(OH)D3 levels and IR (22). These findings were confirmed by other reports (23). Chiui et al showed decreased first and second phase insulin secretion response in vitamin D-deficient subjects (10).…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…One study including subjects in Korea also showed a negative relation between 25(OH)D3 levels and IR (22). These findings were confirmed by other reports (23). Chiui et al showed decreased first and second phase insulin secretion response in vitamin D-deficient subjects (10).…”
Section: Discussionsupporting
confidence: 55%
“…However, some reports have shown that BMI was not different in different vitamin D subgroups (36). Central adiposity is also an important contributor to this association (15,23). We found a higher mean vitamin D level in the insulin-resistant group.…”
Section: Discussionmentioning
confidence: 38%
See 2 more Smart Citations
“…This is in line with the results of the study by Johnson et al (20) who reported that subjects with obesity had low levels of vitamin D, particularly in the males compared with the females, with an odds ratio of 1.41 (95% CI: 1.17-1.70). Other studies that showed low levels of vitamin D in subjects with obesity were among others the studies conducted by Shafinaz et al, (18) Oommen et al, (21) and Tosunbayraktar et al (22) In our study we found a mean adiponectin level of 4.7 ± 0.26 ng/mL in subjects with central obesity, which was significantly lower than the mean adiponectin level of 6.8 ± 0.72 ng/mL in the control group. This showed that subjects with central obesity had lower adiponectin levels compared with the controls.…”
Section: Discussioncontrasting
confidence: 50%